Overuse of Non-caloric Sweeteners in Foods and Beverages in Chile: A Threat to Consumers' Free Choice? - Sambra, Verónica; López-Arana, Sandra; Cáceres, Paola; Abrigo, Karen; Collinao, Javiera; Espinoza, Alexandra; Valenzuela, Sabrina; Carvajal, Bielka; Prado, Gabriel; Peralta, Rebeca; Gotteland, Martin (Frontiers in Nutrition, 2020)
The prevalence of obesity among Chilean adults and children is one of the highest worldwide. To fight the constant increase of non-communicable diseases and the growing sales of sugar-sweetened beverages, the Chilean government recently enacted a new Law of Food Labeling and Advertising imposing the application of front-of-package warning labels in foodstuffs whose composition exceeds limits for critical nutrients including sugar. Accordingly, food companies have been reformulating their products, incorporating non-caloric sweeteners (NCSs) in partial or total replacement of sucrose. The number of NCS-containing foods and beverages, therefore, has been increasing in the last years. This study aims to identify the NCS-containing products from different food/beverage categories currently available on the Chilean market. Nineteen supermarkets and 13 food web pages were visited by trained dietitians to carry out a systematic search of ingredient information from the different food categories. Overall, 1,489 products were analyzed, of which 815 (55.5%) contained at least one NCS, being this proportion particularly high, compared to other countries. 67.1% of the dairy products, 31.5% of the cereal products, 49% of the processed fruits, 74.3% of the non-alcoholic beverages, and 46.2% of sweets and other desserts contained NCS. Considering the food categories more specifically oriented to children, NCSs were present in 98.8% of powder juices, 98.3% of the flavored milks, 91.2% of jellies, and 79% of the dairy desserts. Sucralose and steviol glycosides were the most widely used NCSs, these sweeteners being present, alone or mixed with other, in 73.5 and 39.7% of the NCS-containing products, respectively, while the use of saccharin and cyclamate was low. In addition, 80 tabletop NCSs were available in the local market, 91.2% of them being sucralose and steviol glycosides (alone or combined). The high number of food products containing steviol glycosides makes very plausible that the daily consumption of this NCS in the pediatric populations could exceed its acceptable daily intake (ADI). The fact that there are no NCS-free foods alternatives for certain food categories, especially for children, is worrying.